Comparative Analysis of Company Profitability in The Pandemic Time With 2 Years of Pre-Pandemic - Agus Darmawan; Ana Yuliana Jasuni; Bagja Rahma Putra; Fitrina Lestari (Future Science, 2020)
The purpose of this study was to compare the profitability of companies during the pandemic period with the 2 years pre-pandemic. The population in this study was 27 companies listed on the Indonesia Stock Exchange 2018-2020. The sampling technique was purposive sampling. The sample criteria are (1) Agricultural companies listed on the Indonesia Stock Exchange consecutively for the 2018-2020 period. (2) Agricultural companies listed on the Indonesia Stock Exchange that completely report their financial statements for the first quarter to the third quarter of 2018-2020. The number of samples is 9 agricultural companies. The analysis technique of this research is horizontal comparative analysis and profitability ratio analysis using basic earning power (BEP), Return on equity (ROE), Return on assets (ROA), and profit margin. The results show that COVID-19 has no significant effect on the profitability of agricultural companies, this is evidenced by the conditions of profit and profitability of companies that fluctuate every year. However, it seems that there is one company that has been affected by the pandemic, namely DSFI because the company showed good results in 2018 and 2019. However, in 2020 the company showed not good enough results.